Journal of Foot and Ankle Research - Menz, Hylton; Borthwick, Alan
Journal of Foot and Ankle Research, the official journal of the Australian Podiatry Association and The College of Podiatry (UK), is an open access journal that encompasses all aspects of policy, organisation, delivery and clinical practice related to the assessment, diagnosis, prevention and management of foot and ankle disorders. Journal of Foot and Ankle Research covers a wide range of clinical subject areas, including diabetology, paediatrics, sports medicine, gerontology and geriatrics, foot surgery, physical therapy, dermatology, wound management, radiology, biomechanics and bioengineering, orthotics and prosthetics, as well the broad areas of epidemiology, policy, organisation and delivery of services related to foot and ankle care. The journal encourages submissions from all health professionals who manage lower limb conditions, including podiatrists, nurses, physical therapists and physiotherapists, orthopaedists, manual therapists, medical specialists and general medical practitioners, as well as health service researchers concerned with foot and ankle care. The Australasian Podiatry Association and the College of Podiatry (UK) have reserve funds to cover the article-processing charge for manuscripts submitted by its members. Society members can email the appropriate contact at Australasian Podiatry Association or The College of Podiatry to obtain the corresponding code to enter on submission.